Length polymorphism in the ribosomal DNA intergenic spacers of Lens species - Fernandez, M.=700 1 Ruiz, M.L.; Perez de la Vega, M.
(Es, En)
ilus., 30 ref.
Keywords: HORTALIZAS; LENTEJA; MARCADORS GENETICOS; ESPAÑA